HUBUNGAN ANTARA JUMLAH SESI TERAPI OKSIGENHIPERBARIK SEBAGAI TERAPI ADJUVAN DENGAN PERBAIKAN ULKUS KAKI DIABETIK PADA PASIEN DIRUMAH SAKIT ANGKATAN LAUT DR. MINTOHARDJO TAHUN 2016 - 2018 - Naufal Hilmi Andrisha, (2020)
Introduction: Indonesia is the fourth-highest country with diabetes mellitus patients in the world with 8,4 million population. The significant increase in prevalence has an impact on increase lower extremities disease including diabetic foot ulcers (DFU). Standard care often can't heal diabetic foot ulcers. Adjuvant therapy like hyperbaric oxygen therapy (HBOT) can help in wound bed closure and decrease numbers of diabetic gangrene. This study aims to determine the relationship between total session of HBOT as adjuvant therapy with an improvement of patients DFU.Method: This study uses an analytical observational study design with DFU patients who were given HBOT as adjuvant therapy in Dr. Mintohardjo Naval Hospital in the year 2016 - 2018 as a sample of this study.Results: Friedman test with p-value = 0,001 indicate that there is a relationship between total session of HBOT as adjuvant therapy with an improvement of DFU. Discussion: The total session of HBOT above 10 indicates that it is the most significant improvement for DFU with a decrease in the degree and reduced wound size.